2019
DOI: 10.1111/ajpy.12239
|View full text |Cite
|
Sign up to set email alerts
|

Parental attachment and depressive symptoms in Chinese adolescents: The mediation effect of emotion regulation

Abstract: Objective: We examined if the links between adolescents' parental attachment and depressive symptoms are mediated by emotion regulation (cognitive reappraisal and expressive suppression), and identified which mediator has a stronger mediation effect. Method: The Inventory of Parent and Peer Attachment, Emotion Regulation Questionnaire, and the "Center for Epidemiological Studies-Depression Scale" were distributed to 1955 Chinese adolescents (about 50% boys; 49% in senior high school; aged 10-20 years, M = 14.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…From such communications children can learn to take multiple perspectives and to use cognitive reappraisal strategies when coping with stress. Expressive suppression is a maladaptive strategy that decreases behavioral expression of emotions (Chen et al, 2016 , 2019 ; Goldin et al, 2008 ; Gross, 2001 ). This strategy is used by individuals who lack parental warmth and support to avoid punishment and rejection (Ogbaselase et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From such communications children can learn to take multiple perspectives and to use cognitive reappraisal strategies when coping with stress. Expressive suppression is a maladaptive strategy that decreases behavioral expression of emotions (Chen et al, 2016 , 2019 ; Goldin et al, 2008 ; Gross, 2001 ). This strategy is used by individuals who lack parental warmth and support to avoid punishment and rejection (Ogbaselase et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have further linked emotion regulation strategies to depression (Diedrich et al, 2017 ; Sun et al, 2020 ). As an adaptive strategy, cognitive reappraisal can help reduce negative emotions and improve mental health (Chen et al, 2019 ). In contrast, as a negative emotion regulation strategy, expressive suppression leads to emotion-related physiological problems and depression (Gross & John, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies have demonstrated that low-quality parentchild attachment is associated with internalized psychological problems such as loneliness, depression (Yıldız, 2016), and emotional anorexia nervosa (Laporta-Herrero et al, 2021). adolescents with high-quality parent-child attachment tend to exhibit higher selfefficacy (Chen et al, 2019) and better mental health (Liu et al, 2019;Spruit et al, 2020). Hypothesis 1: Parent-child attachment is a significant positive predictor of adolescent mental health.…”
Section: Introductionmentioning
confidence: 99%
“…The process model has been used extensively in adulthood research; more recently the process model has been applied to childhood and adolescent research (Chen et al, 2019 ; Parsafar & Davis, 2019 ). We incorporated the process model to examine whether executive function and frontal electroencephalogram (EEG) asymmetry (FA) may be important for CR and depressive symptoms among adolescents.…”
Section: Introductionmentioning
confidence: 99%